Pembelajaran Matematika Melalui Problem Posing untuk Meningkatkan Pemahaman dan Kemampuan Aplikasi Siswa terhadap Program Linier - Susi Anika (EduInovasi: Journal of Basic Educational Studies, 2022)
This study starts from the low creativity of students' understanding and the low application activity of students to solve linear programming problems caused by the low ability of teachers to understand learning models in learning activities. The lack of relevance of students' understanding and application skills to linear programming material with a problem posing learning approach. Learning through Problem Posing to improve students' understanding and application skills of linear programming material in class XI TL 1 at SMKN 2 DEPOK. This study uses a quantitative approach. The type of research is the Kemmis model class action research as much as 2 cycles. The steps taken are planning, implementation, observation and reflection. Data collection techniques through observations of teacher activities, student activities, test understanding of learning outcomes, student response questionnaires and interviews. Data analysis used quantitative and descriptive qualitative analysis by determining the percentage of the average score of activities and the completeness of student learning outcomes, then determining the criteria for success. The results obtained in the learning process carried out by teachers and student activities by applying the problem positioning approach were very good and there was an increase of 17.63% for teachers and 13.3% for students. Therefore, it can be concluded that the use of the problem posing approach is very influential in understanding and improving students' abilities. The results of this study are expected to be useful to support learning innovation in order to improve learning in order to improve school quality. Keywords: problem posing, understanding, mathematics, linear programming